MONETARY POLICY AND TELECOMMUNICATION OUTPUT IN NIGERIA - John Abiodun Akinde; Elijah Oludayo (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2020)
Different policies impact on the growth of the telecommunication sector in Nigeria. One of these policies which influence the expansion or contraction of the telecommunication output is monetary policy. To this end, this research examined the effect of monetary policy on telecommunication output in Nigeria. For the purpose of analysis, time series secondary data were sourced from Central Bank of Nigeria (CBN) statistical bulletin covering the periods1986 to 2018. Autoregressive Distributed Lag (ARDL) technique was employed after examining the stationarity of the data series using Augmented Dickey-Fuller technique. The bound co-integration test revealed that there is long run equilibrium between the monetary policy variables employed and telecommunication output. The ARDL result revealed that money supply had significant and positive effect on telecommunication output in the short and long run; liquidity ratio produced an insignificant and negative relationship with telecommunication output in the short run and insignificant positive effect in the long run; exchange rate had insignificant negative effect in the short run and a significant positive effect on telecommunication output in the long run; consumer price index had significant negative influence on telecommunication outputboth in the short run and long run. The study concluded that monetary policy stimulates telecommunication output in Nigeria. Thus, it was recommended that the monetary authority should pursue an expansionary monetary policy to sustain the positive influence of money supply on telecommunication output in Nigeria while rolling out policy to reduce the liquidity ratio of banks in the short run but increase it in the long run so that the long term favourable effect of liquidity ratio can be felt on telecommunication output.